The Effect of Tofu and Fermented Coconut Dregs on Body Weight Gain and Cocoon Production of African Worms (Eudrilus eugeniae) - Rakhmatdi Rakhmatdi; Dewi Puspita Sari (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Earthworms are currently in great demand for industrial and pharmaceutical needs, so it is necessary to increase the productivity of worms by breeders. This study aims to determine the effect of giving tofu pulp and coconut pulp on body weight gain and cocoon production of Eudrilus eugeniae worms. The object of this research is Eudrilus eugeniae which has been clit. This study was divided into two groups, namely control and treatment with six replications each so that there were 24th experimental units. In the control and treatment groups, the researchers included 10th Eudrilus eugeniae worms in each treatment in the form of a combination of tofu pulp and coconut pulp. Parameters observed were worm biomass and several cocoons. The data on the weight gain of the worms were analyzed using One Way Anova and then continued with the Duncan Multiple Test (DMRT) with significantly different results. Furthermore, data on the number of worm cocoons were analyzed using the Kruskal Wallis test. The results showed that the provision of tofu and coconut pulp had a significant effect on body weight gain and the production of Eudrilus eugeniae cocoons. There is an effect of giving tofu dregs and fermented coconut pulp on the increase in body mass of Eudrilus eugeniae worms as a conclusion.